Distribution of Human T-Lymphotropic Virus (HTLV) and Hepatitis C Co-infection in Bahia, Brazil - Pereira, Felicidade Mota (2020)
Coordination of Superior Level Staff Improvement- Brazil (CAPES) - Finance Code 001 and National Foundation for the Development of Private Higher Education (FUNADESP), grants 9600140 and 9600141. Maria Fernanda R. Grassi and Bernardo Galvão-Castro are research fellows of CNPq (process no. 304811/2017-3 and 311054/2014-5, respectively).